A method for realizing in-situ exfoliation of two-dimensional fillers using highly elastic polymers
By using high elastic polymers to generate strong shear stress during the melt processing, the in-situ peeling and dispersion of two-dimensional fillers is achieved, and the problems of large solvent consumption, complex steps and low yield in the prior art are solved, and efficient and low-cost two-dimensional nanomaterial preparation is achieved.
Patent Information
- Application Number
- CN202211031810.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-26
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-08-26
AI Technical Summary
The existing two-dimensional filler peeling method requires the use of a large number of solvents, which are complicated, have low yield, high cost, and have strict requirements on conditions, have high energy consumption, long cycles, and are prone to damage the transverse dimensions of the two-dimensional filler, limiting its performance in polymer composite materials.
The high elastic polymer is used to heat up through the equipment and provide strong stress in the melt processing equipment, causing the polymer to flow forcibly and generate strong shear stress, thereby mixing two-dimensional filler powder into the flowing polymer to achieve in-situ peeling and dispersion of the two-dimensional filler.
Solvent-free, simple steps, high yield and low cost two-dimensional filler peeling is achieved, which reduces the demanding requirements on conditions, avoids the lateral dimensional damage of the two-dimensional filler, and can effectively achieve in-situ dispersion and peeling of two-dimensional nanomaterials in polymer composite materials.
Smart Images

Figure CN115490889B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanofillers, and in particular to a method for realizing in-situ stripping of two-dimensional fillers by utilizing highly elastic polymers. Background Art
[0002] With the continuous development of polymer composites, the morphology and size of fillers as important structural parameters also play a very important role. Among them, two-dimensional nanomaterials are anisotropic, and have different physical and chemical properties in the perpendicular and parallel directions. Therefore, the in-plane size and thickness of two-dimensional nanomaterials will directly affect the mechanical, heat resistance, electrical conductivity, thermal conductivity, barrier, electromagnetic shielding and other properties and functions of polymer-based composites. Among them, the preparation of two-dimensional nanomaterials with lower thickness is the main direction of high-performance and multifunctional modification of composite materials. The stripping of existing two-dimensional fillers can significantly reduce their thickness and give full play to the characteristics of two-dimensional fillers in composite materials. A typical example is the stripping of graphite into graphite nanosheets or graphene. The stripped graphite gives the composite material better properties.
[0003] Existing stripping methods require the use of a large amount of solvents and the steps are cumbersome, and the requirements for different two-dimensional fillers are different, such as specific dispersion solvents, specific dispersion equipment methods and post-processing conditions, etc.; and the existing methods have low yields, high costs, and demanding conditions; some methods have high energy consumption, long cycles, and large damage to the lateral dimensions of the two-dimensional fillers. In addition, it also has a natural deficiency when compounded with polymers, that is, it needs to be dispersed again in the polymer matrix, and the size of the stripping does not represent the final size in the composite material (directly affected by the dispersion effect). This limits the size effect of the two-dimensional filler in the polymer composite material. Therefore, it is crucial to the development of composite materials to invent a simple, efficient, green and environmentally friendly method for stripping two-dimensional fillers without solvents. Summary of the invention
[0004] The present invention aims to provide a method for in-situ exfoliation of two-dimensional fillers using highly elastic polymers, so as to solve the problems that the existing exfoliation methods require the use of a large amount of solvents and the steps are cumbersome, and the requirements for different two-dimensional nanofillers are different. In addition, the existing methods have low output, high cost, harsh conditions or high energy consumption, long cycles, and great damage to the lateral dimensions of the two-dimensional fillers.
[0005] In order to achieve the above object, the basic scheme of the present invention is as follows: a method for realizing in-situ exfoliation of two-dimensional fillers using highly elastic polymers, comprising the following steps:
[0006] Step 1, heating the polymer by a device to make the polymer in a highly elastic state;
[0007] Step 2: applying strong stress to the polymer in a highly elastic state through processing equipment, so that the highly elastic polymer is forced to flow, and the molecular chains of the polymer in the forced flow undergo irreversible molecular motion, thereby generating strong shear stress;
[0008] Step 3, directly mixing the unpeeled two-dimensional filler powder into the flowing high-elastic polymer, so that the strong shear stress in the flowing high-elastic polymer matrix can act on the two-dimensional filler;
[0009] Step 4: After the mixed sample is subjected to forced flow processing for a certain period of time, all the two-dimensional fillers are subjected to shearing and exfoliation by fully saturated strong shear stress, and finally dispersed two-dimensional nanomaterials with successful in-situ exfoliation are obtained.
[0010] Principle of the basic solution: This method uses the extremely high viscosity of highly elastic polymers. When they flow under external force, they will generate great stress, which can effectively destroy and deform the two-dimensional fillers dispersed in them, and make the two-dimensional fillers start to be destroyed from the weak layers. Polymers in the highly elastic state have special molecular chain movement behavior. When there is no external force to make them flow, the molecular chains will not have free thermal movement. This means that each time the polymer in the highly elastic state is forced to flow, it can effectively apply force to the two-dimensional filler, and the molecular chain will automatically fill in the peeled position, and the two-dimensional filler peeled by external force will not be reunited due to molecular thermal motion. These characteristics of highly elastic polymers enable the two-dimensional filler to be continuously peeled off, and ultimately obtain two-dimensional nanomaterials.
[0011] Advantages of the basic solution: It solves the problems of existing stripping methods that require the use of large amounts of solvents and have cumbersome steps, and that different two-dimensional nanofillers have different requirements. The existing methods also have low yields, high costs, demanding conditions or high energy consumption, long cycles, and significant damage to the lateral dimensions of the two-dimensional fillers.
[0012] Furthermore, the specific process of step one is: the polymer is heated to between the glass transition temperature and the viscosity flow temperature through the equipment, so that the polymer becomes an amorphous polymer between the glass transition temperature and the viscosity flow temperature, so that the chain segments of the polymer are in a movable state and the molecular chain has no thermal motion.
[0013] The principle of the basic solution: The polymer is heated to between the glass transition temperature and the viscosity flow temperature through the equipment, so that the polymer is in a highly elastic state.
[0014] Furthermore, the specific process of step 2 is: providing strong stress to the polymer in the highly elastic state through melt processing equipment to force the highly elastic polymer to flow, and using mechanical equipment to make the flowing highly elastic polymer produce strong shear stress.
[0015] Furthermore, the specific process of step 4 is: the blends in steps 1, 2 and 3 are packaged and milled once or multiple times to obtain a monodispersed two-dimensional nanofiller masterbatch in a highly elastic polymer medium.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0017] (1) It does not require the use of a large amount of solvent and the steps are simple, and it can be applied to different two-dimensional nanofillers, such as etc.; and the method has high yield, low cost, and is not demanding on conditions; and it has little damage to the lateral dimensions of the two-dimensional nanofillers.
[0018] (2) Highly elastic polymers have extremely high viscosity. When they flow under external force, they will generate great stress, which can effectively destroy and deform the two-dimensional nanofillers dispersed in them, causing the two-dimensional fillers to be destroyed from the weak interlayers. Polymers in the highly elastic state have special molecular chain movement behavior. When there is no external force to make them flow, the molecular chains will not have free thermal movement. This means that each time the polymer in the highly elastic state is forced to flow, it can effectively apply force to the two-dimensional nanofillers, and the molecular chains will automatically fill in the peeled position, without the two-dimensional nanofillers peeled by external force reuniting due to molecular thermal movement. These characteristics of highly elastic polymers enable the two-dimensional nanofillers to be continuously peeled off.
[0019] (3) Green and environmentally friendly, no toxic or harmful products are used or produced; highly efficient and energy-saving, capable of stripping two-dimensional fillers on a large scale in a short time; in-situ stripping, the stripped two-dimensional filler material is monodispersed in the polymer matrix and can be used directly or as a masterbatch; it has a wide range of applicability, is effective for all kinds of highly elastic polymers, and has a certain stripping effect on various two-dimensional fillers.
[0020] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a flow chart of a method for realizing in-situ exfoliation of two-dimensional fillers using highly elastic polymers provided in an embodiment of the present invention;
[0022] Figure 2 is a scanning electron microscope (SEM) image of the graphite powder used in Experiment 1 of the present invention;
[0023] Figure 3 is a scanning electron microscope (SEM) image of in-situ dispersion of graphite after exfoliation in Experiment 1 of the present invention;
[0024] Figure 4 is a scanning electron microscope SEM image of the boron nitride powder used in Experiment 2 of the present invention;
[0025] Figure 5 is a scanning electron microscope SEM image of the boron nitride after exfoliation and in-situ dispersion in Experiment 2 of the present invention;
[0026] Figure 6 This is a scanning electron microscope (SEM) image of graphite exfoliation and dispersion at high content in Experiment 3 of the present invention. DETAILED DESCRIPTION
[0027] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0028] The following is further described in detail through specific implementation methods:
[0029] The embodiment is basically as shown in the attached Figure 1 and attached Figure 2 As shown: A method for realizing in-situ exfoliation of two-dimensional fillers using highly elastic polymers, comprising the following steps:
[0030] Step 1, heating the polymer by a device to make the polymer in a highly elastic state;
[0031] Step 2: applying strong stress to the polymer in a highly elastic state through processing equipment, so that the highly elastic polymer is forced to flow, and the molecular chains of the polymer in the forced flow undergo irreversible molecular motion, thereby generating strong shear stress;
[0032] Step 3, directly mixing the unpeeled two-dimensional filler powder into the flowing high-elastic polymer, so that the strong shear stress in the flowing high-elastic polymer matrix can act on the two-dimensional filler;
[0033] Step 4: After the mixed sample is subjected to forced flow processing for a certain period of time, all the two-dimensional fillers are subjected to shearing and exfoliation by fully saturated strong shear stress, and finally dispersed two-dimensional nanomaterials with successful in-situ exfoliation are obtained.
[0034] The specific implementation process is as follows: This method utilizes the extremely high viscosity of the highly elastic polymer, which will generate great stress when it flows under external force, and can effectively cause the two-dimensional fillers dispersed therein to be destroyed and deformed, so that the two-dimensional fillers are destroyed from the weak interlayers. The polymer in the highly elastic state has a special molecular chain movement behavior. When there is no external force to make it flow, the molecular chain will not have free thermal movement. This results in that each time the polymer in the highly elastic state is forced to flow, it can effectively apply force to the two-dimensional filler, and the molecular chain will automatically fill in the peeling position, and the two-dimensional filler peeled by external force will not be reunited due to molecular thermal motion. These characteristics of highly elastic polymers enable the two-dimensional filler to be continuously peeled off, and ultimately obtain a two-dimensional nanomaterial.
[0035] The specific process of step one is: the polymer is heated to between the glass transition temperature and the viscosity flow temperature through the equipment, so that the polymer becomes an amorphous polymer between the glass transition temperature and the viscosity flow temperature, so that the chain segments of the polymer are in a movable state and the molecular chain has no thermal motion.
[0036] The specific implementation process is as follows: the polymer is heated to between the glass transition temperature and the viscosity flow temperature through the equipment, so that the polymer is in a highly elastic state.
[0037] The specific process of step two is: provide strong stress to the polymer in the highly elastic state through melt processing equipment, so that the highly elastic polymer is forced to flow, and use mechanical equipment to make the flowing highly elastic polymer produce strong shear stress.
[0038] The specific process of step 4 is: the blends in step 1, step 2 and step 3 are packaged and milled once or multiple times to obtain a monodispersed two-dimensional nanofiller masterbatch in a highly elastic polymer medium.
[0039] In order to prove the creativity and technical value of the technical solution of the present invention, this section conducts experiments and comparative experiments on specific products or related technologies for the technical solution of the claims.
[0040] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0041] Experiment 1:
[0042] A method for in-situ exfoliation of two-dimensional fillers using highly elastic polymers is achieved by the following scheme:
[0043] (1) Weigh 59.5 g of polylactic acid 4060D (NatureWorks) and 6.5 g of graphite, and dry the polylactic acid and graphite in a vacuum oven at 50° C. for 5 hours.
[0044] (2) A two-roll mill was used with a temperature of 90°C, a front roll speed of 10 rpm, a rear roll speed of 8 rpm, and a front and rear roll distance of 0.15 mm.
[0045] (3) Feed the dried polylactic acid into a double-roll mill and add the dried graphite when the polylactic acid flows between the rollers.
[0046] (4) Take out the roll sample and make a triangle package, then feed it back into the mixing mill and repeat 7-8 times.
[0047] (5) Take out the sheet sample for the last time and cool it to room temperature.
[0048] As attached Figure 2 and attached Figure 3 As shown, it shows that graphite has achieved in-situ exfoliation and in-situ dispersion.
[0049] Experiment 2:
[0050] (1) Weigh 52 g of polylactic acid 4060D (NatureWorks) and 13 g of boron nitride, and dry the polylactic acid and boron nitride in a vacuum oven at 50° C. for 5 hours.
[0051] (2) A two-roll mill was used with a temperature of 90°C, a front roll speed of 10 rpm, a rear roll speed of 8 rpm, and a front and rear roll distance of 0.15 mm.
[0052] (3) Feed the dried polylactic acid into a double-roll mill and add the dried boron nitride when the polylactic acid flows between the rollers.
[0053] (4) Take out the roll sample and make a triangle package, then feed it back into the mixing mill and repeat 7-8 times.
[0054] (5) Take out the sheet sample for the last time and cool it to room temperature.
[0055] As attached Figure 4 and attached Figure 5 As shown, the difference between Experiment 2 and Experiment 1 is that the two-dimensional filler used is changed from graphite to hexagonal boron nitride, which can still achieve exfoliation and in-situ dispersion.
[0056] Experiment 3:
[0057] (1) Weigh 40 g of polylactic acid 4060D (NatureWorks) and 40 g of graphite, and dry the polylactic acid and graphite in a vacuum oven at 50° C. for 5 hours.
[0058] (2) A two-roll mill was used with a temperature of 90°C, a front roll speed of 10 rpm, a rear roll speed of 8 rpm, and a roll gap of 0.15 mm.
[0059] (3) Feed the dried polylactic acid into a double-roll mill and add the dried graphite when the polylactic acid flows between the rollers.
[0060] (4) Take out the roll sample and make a triangle package, then feed it back into the mixing mill and repeat 7-8 times.
[0061] (5) Take out the sheet sample for the last time and cool it to room temperature.
[0062] As attached Figure 6 As shown, the difference between Experiment 3 and Experiment 1 is that the content of graphite increases from 10wt% to 50wt%, as shown in Figure 6 As shown, at high content, graphite was also exfoliated and dispersed in situ in the polymer matrix.
[0063] Experiment 4:
[0064] (1) Weigh 65 g of polycarbonate PC and 43 g of graphite, and dry the polycarbonate and graphite in a vacuum oven at 120° C. for 5 hours.
[0065] (2) A two-roll mill was used with a temperature of 170°C, a front roll speed of 10 rpm, a rear roll speed of 8 rpm, and a front and rear roll distance of 0.15 mm.
[0066] (3) Feed the dried polycarbonate into a double-roll mill and add the dried graphite while the polycarbonate is flowing between the rollers.
[0067] (4) Take out the roll sample and make a triangle package, then feed it back into the mixing mill and repeat 7-8 times.
[0068] (5) Take out the sheet sample for the last time and cool it to room temperature.
[0069] Experiment 5:
[0070] (1) Weigh 65 g of polymethyl methacrylate (PMMA) (NatureWorks) and 43 g of graphite, and place the polymethyl methacrylate and carbon nanotubes in a vacuum oven at 120° C. and dry for 5 hours.
[0071] (2) A two-roll mill was used with a temperature of 150°C, a front roll speed of 10 rpm, a rear roll speed of 8 rpm, and a front and rear roll distance of 0.15 mm.
[0072] (3) Feed the dried polymethyl methacrylate into a double-roll mill and add the dried graphite when the polymethyl methacrylate flows between the rolls.
[0073] (4) Take out the roll sample and make a triangle package, then feed it back into the mixing mill and repeat 7-8 times.
[0074] (5) Take out the sheet sample for the last time and cool it to room temperature.
[0075] Experiment 6:
[0076] (1) Weigh 40 g of polylactic acid 4060D (NatureWorks) and 40 g of montmorillonite, and dry the polylactic acid and montmorillonite in a vacuum oven at 50° C. for 5 hours.
[0077] (2) A two-roll mill was used with a temperature of 90°C, a front roll speed of 10 rpm, a rear roll speed of 8 rpm, and a roll gap of 0.15 mm.
[0078] (3) Feed the dried polylactic acid into a double-roll mill and add the dried montmorillonite while the polylactic acid is flowing between the rollers.
[0079] (4) Take out the roll sample and make a triangle package, then feed it back into the mixing mill and repeat 7-8 times.
[0080] (5) Take out the sheet sample for the last time and cool it to room temperature.
[0081] Some positive effects achieved by the present invention during the development or use process do have great advantages compared with the prior art, which are described below in conjunction with data, charts, etc. of the experimental process.
[0082] Experiments 4 and 5 used higher glass transition materials as the dispersion matrix to also achieve the exfoliation and in-situ dispersion of graphite.
[0083] Experiment 6 is the contribution of the present invention to the dispersion of other two-dimensional fillers.
[0084] The above is only an embodiment of the present invention, and the common knowledge such as the known specific structure and / or characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for in-situ exfoliation of two-dimensional fillers using a highly elastic polymer, characterized in that: The steps include: Step 1: The polymer is heated to a temperature between the glass transition temperature and the viscosity flow temperature by a device, so that the polymer is in a highly elastic state, so that the polymer chain segments are in a movable state and the molecular chain has no thermal motion; Step 2: applying strong stress to the polymer in a highly elastic state through processing equipment, so that the highly elastic polymer is forced to flow, and the molecular chains of the polymer in the forced flow undergo irreversible molecular motion, thereby generating strong shear stress; Step 3, directly mixing the unpeeled two-dimensional filler powder into the flowing high-elastic polymer, so that the strong shear stress in the flowing high-elastic polymer matrix can act on the two-dimensional filler; Step 4: After the mixed sample is subjected to forced flow processing for a certain period of time, all the two-dimensional fillers are subjected to shearing and exfoliation by fully saturated strong shear stress, and finally dispersed two-dimensional nanomaterials with successful in-situ exfoliation are obtained; The specific process of step 2 is: providing strong stress to the polymer in the highly elastic state through melt processing equipment to force the highly elastic polymer to flow, and using mechanical equipment to make the flowing highly elastic polymer produce strong shear stress.
2. The method for realizing in-situ exfoliation of two-dimensional fillers using highly elastic polymers according to claim 1, characterized in that: The specific process of step 4 is: packing and refining the blend in step 3 for multiple times to obtain a two-dimensional nanofiller masterbatch that is in-situ exfoliated and uniformly dispersed in a highly elastic polymer medium.